The Dark Side of Interorganizational Relationships: An Integrative Review and Research Agenda. (January 2019) - Oliveira, Nuno; Lumineau, Fabrice
Scholars across management fields have paid increasing attention to the dark side of interorganizational relationships. We first summarize the concept of the "dark side" and its manifestations in interorganizational relationships. We then map the main findings on the antecedents, consequences, and moderating factors of the dark-side manifestations. We relate research gaps to opportunities in our integrative framework. Furthermore, we present a research agenda to advance theory on the manifestation characteristics, the entities and their motivations, the temporality issues, and the positive outcomes of dark-side manifestations.